Crystallization and preliminary X‐ray analysis of peptidyl‐tRNA hydrolase from Thermus thermophilus HB8. Issue 3 (24th March 2013) - Matsumoto, Ami; Shimizu, Yoshihiro; Takemoto, Chie; Ueda, Takuya; Uchiumi, Toshio; Ito, Kosuke
<x xml:space="preserve">Abstract</x> Peptidyl‐tRNA is produced from the ribosome as a result of aborted translation. Peptidyl‐tRNA hydrolase cleaves the ester bond between the peptide and the tRNA of peptidyl‐tRNA molecules, to recycle tRNA for further rounds of protein synthesis. In this study, peptidyl‐tRNA hydrolase from Thermus thermophilus HB8 (TthPth) was crystallized using 2‐methyl‐2, 4‐pentanediol as a precipitant. The crystals belonged to the orthorhombic space group P212121, with unit‐cell parameters a = 47.45, b = 53.92, c = 58.67 Å, and diffracted X‐rays to atomic resolution (beyond 1.0 Å resolution). The asymmetric unit is expected to contain one TthPth molecule, with a solvent content of 27.13% (VM = 1.69 Å3 Da−1). The structure is being solved by molecular replacement.